2017
DOI: 10.1007/978-3-319-68445-1_30
|View full text |Cite
|
Sign up to set email alerts
|

Pairwise Ising Model Analysis of Human Cortical Neuron Recordings

Abstract: Abstract. During wakefulness and deep sleep brain states, cortical neural networks show a different behavior, with the second characterized by transients of high network activity. To investigate their impact on neuronal behavior, we apply a pairwise Ising model analysis by inferring the maximum entropy model that reproduces single and pairwise moments of the neuron's spiking activity. In this work we first review the inference algorithm introduced in Ferrari, Phys. Rev. E (2016) [1]. We then succeed in applyin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…The inference can thus be performed by an ascendant dynamics that requires to estimate model averages of observables. For the Ising model we applied the Markov-Chain Monte-Carlo method introduced in [3,10]. For the one population model, we applied the Newton dynamics proposed in [5] For the two-population model, we modify the algorithm of [5] to take into account two populations.…”
Section: B Inference Methodsmentioning
confidence: 99%
“…The inference can thus be performed by an ascendant dynamics that requires to estimate model averages of observables. For the Ising model we applied the Markov-Chain Monte-Carlo method introduced in [3,10]. For the one population model, we applied the Newton dynamics proposed in [5] For the two-population model, we modify the algorithm of [5] to take into account two populations.…”
Section: B Inference Methodsmentioning
confidence: 99%
“…Note that although our framework for constructing the rs-SC does not explicitly model brain activity at a neuronal level, several seminal studies have used the Ising model to investigate neuronal firing patterns with success, showing that ensemble level activities can be well explained by pairwise Ising interactions [24,57]. To be clear, from a connectomics perspective, if several brain regions are identified to have an increase in positive edges in the rs-SC, collectively, that would suggest a wider-spread pattern of coupling (i.e., more likely to exhibit a pattern of global coupling) that may subserve hyperexcitation.…”
Section: Mri and Pet Imagingmentioning
confidence: 99%
“…The Ising model for spin glasses (Jaynes, 1982) fitted to neural data (Schneidman et al, 2006) has revealed divergent types of emergent neuronal dynamics in conscious and unconscious states. While neuronal interactions are pairwise in wakefulness (Nghiem et al, 2017), coupling becomes population-wide in deep sleep (Tavoni et al, 2017; Nghiem et al, 2018b). In particular, inhibitory neurons organize synchronous activity across populations (Nghiem et al, 2018b; Zanoci et al, 2019), especially during deep sleep (Peyrache et al, 2012; Le Van Quyen et al, 2016; Olcese et al, 2016) where inhibitory neurons regulate rhythms of slow wave dynamics (Compte et al, 2008; Funk et al, 2017; Zucca et al, 2017, 2019).…”
Section: Microscopic Mechanisms; Biophysics Of Brain Statesmentioning
confidence: 99%